Studies on Seasonal Abundance and Correlation of Major Groups of Insect-Pests and their Natural Enemies in Rice Ecosystem - Zhimomi, V. Akashe; Ao, M. Alemla (International Journal of Bio-resource and Stress Management, 2023)
Studies on seasonal abundance of major insect pests and their natural enemies was carried out at three different altitudes viz. lowland, foothill and upland during September 2002-August 2004. A mean total of 2173.7, 1114.1 and 525.7 of major insect pests were recorded respectively from lowland, foothill and upland rice ecosystems. Natural enemies were recorded with a mean total number of 727, 538.4 and 257.8 from the three respective rice fields. The major seasonal abundance of the major insect pests were most active from the month of May-November while minimum was recorded mostly during January-March in al the three ecosystems, with temperature record of 31.8°C (max.) and 12.2°C (min.). The temperature plays an important role as it affects the activities of Arthropods, causes increase or decrease their population size. The correlation coefficient value (r) had revealed a positive effect of natural enemies on all the population of major insect pests.